Clipping and coiling of intracranial aneurysms in the elderly patients: clinical features and treatment outcomes - Chen, Cheng; Qiao, Hao; Cui, Zhenwen; Wang, Chao; Zhang, Chonghui; Feng, Yugong (Frontiers in Neurology, 2023)
Objective In recent years, more and more cases of intracranial aneurysms (IAs) have been found in elderly patients, and neurosurgical interventions have increased, but there is still no consensus on the best treatment strategy for elderly patients. In elderly patients, endovascular coiling (EC) is more popular than surgical clipping (SC) due to its advantages of less trauma and faster recovery. However, SC has made great progress in recent years, significantly improving the prognosis of elderly patients. Therefore, it is necessary to further explore the effects of different treatment modalities on clinical prognosis, hospital stay, and hospital cost of elderly IA patients, and select the most appropriate treatment modalities. Methods The authors retrospectively analyzed 767 patients with intracranial aneurysms admitted to the facility between August 2017 and December 2022. Prognostic risk factors and multivariate logistic regression were analyzed for elderly patients treated with EC or SC. The area under the receiver operating characteristic (ROC) curve was used to calculate the predictive power of each independent predictor between the treatment groups. Results Our study included 767 patients with aneurysms, of whom 348 (45.4%) were elderly, 176 (22.9%) underwent endovascular coiling, and 172 (22.4%) underwent microsurgical clipping. A comparison of elderly patients treated with EC and SC showed a higher prevalence of hypertension in the EC group (P = 0.011) and a higher Hunt–Hess score on admission in the SC group (P = 0.010). Patients in the EC group had shorter hospital stays but higher costs (P = 0.000 and P = 0.000, respectively). Patients treated with SC had a higher incidence of postoperative cerebral infarction and poor prognosis (P = 0.002 and P = 0.008, respectively). Through multi-factor logistic analysis, it was found that age (OR 1.209, 95% CI 1.047–1.397, P = 0.010), length of stay (LOS) (OR 1.160, 95 CI% 1.041–1.289, P = 0.007), and complications (OR 31.873, 95 CI% 11.677–320.701, P = 0.000) was an independent risk factor for poor prognosis in elderly patients with EC. In elderly patients treated with SC, age (OR 1.105, 95% CI 1.010–1.209, P = 0.029) was an independent risk factor for poor prognosis. Conclusion EC and SC interventions in elderly adults carry higher risks compared to non-older adults, and people should consider these risks and costs when making a decision between intervention and conservative treatment. In elderly patients who received EC or SC treatments, EC showed an advantage in improving outcomes in elderly patients although it increased the economic cost of the patient's hospitalization.